A Families Functional Support for Breast Cancer Survivor at Haji Adam Malik Hospital, Medan 2020 - Lubis, Namora Lumongga; Hasnida, H; Novitarum, Lilis (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2020)
Purpose: The purpose of this study was to identify family function support for breast cancer survivors at Haji Adam Malik Hospital Medan.Methodology: This study used a descriptive method with a sample size of 40 people. This study used consecutive sampling technique. The sample in this study were breast cancer patients who were undergoing a series of therapies at the Haji Adam Malik Hospital Medan. Variable family support was measured by a questionnaire distributed to breast cancer patients. The questionnaire consisted of 40 questions covering support for religious, love, economic and protection functions. Family support assessments use positive and negative criteria. Positive criteria show that the family supports breast cancer sufferers in carrying out the therapy. The negative criteria show that the family is less supportive of breast cancer sufferers in carrying out the therapy.Results: The results showed that 82.5% positive family function support (82.5%) and 17.25% negative family function support. Family function support is generally positive. Families functional support from the highest to the lowest functions is the religious function (85%), the love function (82.50%), the economic function (82.50%) and the protection function (77.50%).Applications / Originality / Value: It is hoped that the family can increase family support in the protection function by providing a sense of security and feeling protected.